Preparation of nanoparticulate TiO2 containing nanocrystalline phases of anatase and brookite by electrochemical dissolution of remelted titanium components - Ortega Díaz, D.; Fernández, D.; Sepúlveda, S.; Lindeke, R. R.; Pérez Bueno, J. J.; Peláez Abellán, E.; Manríquez, J. (Elsevier, 2020)
In this investigation, we present an efficient electrochemical methodology to prepare nano-particulate TiO2 having a nano-crystalline composition of 40% Anatase and 60% Brookite, without need for subsequent thermal treatments (which are typically applied to alter the amount of amorphicity). This procedure for oxide synthesis is novel as it involves the galvanostatic dissolution of remelted Titanium Components, thus constituting a promising technological route for re-using Titanium-containing metallic pieces from the secondary metals industry to produce nanocrystalline TiO2 powders as a high value-added primary product. The experimental results presented showed that the faradaic efficiency of the TiO2 electro-synthesis, crystalline purity, and dispersion of the electro-generated TiO2 material was significant, despite the fact that the titanium content of the remelted titanium components was less than 80%.